Práticas dialógicas na educação física escolar: problematizando a desigualdade de gênero nos esportes de invasão - Floriano, Cristiano Lima (Universidade Federal de São Carlos, 2025)
Motivated by the persistent gender inequalities in Physical Education classes, this study aimed to analyze the educational processes emerging from dialogical pedagogical practices in the context of invasion sports, with a view to promoting gender equity. The research, with a qualitative approach and based on action research methodology, was carried out with a 6th-grade class from a public school in Ribeirão Preto (SP), composed of 30 students (17 girls and 13 boys). A didactic unit was implemented, structured from the principles of the Methodology of Critical-Affective Experience (MECA), which values dialogue, affectivity, and the problematization of bodily experiences. Data were collected through the teacher-researcher’s class diaries and conversation circles with the students. The data analysis followed the thematic coding method (Bogdan & Biklen, 1994), from which two main categories emerged: (1) Gender Stereotypes in Sport, with subcategories such as the invisibilization of women athletes and the overvaluation of male performance; and (2) Inclusion and Change of Mindset, highlighting the increased participation of girls, greater cooperation between genders, and the construction of a more democratic environment. The results showed significant progress in the participation of girls, with greater protagonism, self-confidence, and appropriation of sports spaces. Changes in the attitudes of boys were also observed, as they began to recognize and value the active presence of their female peers. The experience demonstrated that practices based on listening, dialogue, and critical mediation contribute to overcoming stereotypes and transform Physical Education into a meaningful learning space for all. It is concluded that active, affective, and coeducational methodologies can support fairer and more emancipatory pedagogical practices, reinforcing the importance of continuous teacher training focused on gender equity and social transformation.
Dialogical practices in school physical education: problematizing gender inequality in invasion sports
Keywords: Educação Física Escolar; Esportes de Invasão; Igualdade de Gênero; Ensino Fundamental; Dialogicidade; School physical education; Invasion sports; Gender equality; Elementary school; Dialogicality; CIENCIAS DA SAUDE::EDUCACAO FISICA